Formation and Evolution of Supradetachment Basins During Continental Extension: Insights From the Fuxin Basin in NE China - Sun, Shouheng; Qiu, Liang; Yan, Dan-Ping; Zhou, Zhicheng; Zhang, Jiaming; Wang, Xin; Wu, Bingwei; Shi, Haitao; Ariser, Shahnawaz; Chu, Rong; Fu, Yu; Wang, Yini (Frontiers in Earth Science, 2022)
Supradetachment basins can record the stratigraphy and development of metamorphic core complexes (MCCs). The Fuxin supradetachment basin, which lies immediately to the west of the Yiwulvshan MCC in NE China, provides an excellent opportunity to establish the relationship between supradetachment basins and MCCs. In this study, we conducted field investigations, sedimentary facies analysis, and seismic profile interpretation to decipher the sedimentary processes and structural evolution of the basin and link them to the development of the Yiwulvshan MCC. The Fuxin Basin is filled predominantly by syn-rift volcanic sedimentary and post-rift clastic rocks, which developed in four stages, namely, proto-rift, fault subsidence, transition, and compression. The Fuxin Basin developed simultaneously with the two stages (earlier faulting-dominated and later exhumation stages) of development of the MCC. Erosion of the core of the Yiwulvshan MCC provided clastic material to the Fuxin Basin. On the basis of multi-stage reconstruction of the formation and evolution of the Fuxin Basin and Yiwulvshan MCC, we propose that rollback of the Paleo-Pacific Plate and retreat of the subduction trench provided the geodynamic setting for the crustal extension that formed the basin and MCC.